PERDARAHAN POSTPARTUM (PERDARAHAN PASKASALIN) - Simanjuntak, Leo (LPPM Universitas HKBP Nommensen, 2020)
Postpartum hemorrhage is the leading cause of maternal death worldwide with 5 – 10% of incidence. The etiology of postpartum hemorrhage are uterine atony, retensio placentae, genital tract laceration, retained placental tissue and coagulation disorders. It was estimated 2 hours period from the onset of postpartum hemorrhage toward the maternal death, meanwhile it was 12 hours in antepartum hemorrhage. It is therefor early diagnosis and prompt management is essential. The solid and skilled teamwork is needed in order to successfully manage postpartum hemorrhage and to avoid maternal death.